Language Vitality Indicator Towards The Use Of Ternate Language On Ternate Language Enclave In Sahu District, West Halmahera Regency - Nurain Jalaludin; Rahma Do Subuh; Ismail Maulud; Bakhtiar Haerullah (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
Language vitality is a tool used to assess how well speakers of a language in expressing their language. One of the languages of North Maluku is Ternate, which is spoken not only on Ternate Island but also in the West Halmahera area. The Sahu district's coastal areas are home to the majority of Ternate language speakers. The purpose of this study is to measure factors that affect the use of Ternate language and language vitality of Ternate language enclave in Sahu district, West Halmahera Regency. The method used is descriptive qualitative with data collection techniques in the form of observation and structured interviews with instruments in the form of questionnaires. A summary of the state of Ternate language in the Sahu district is then obtained by applying the language vitality theory to the data analysis. The results indicate that adults (≥30 years) in Sahu district’s villages of Lako, Jarakore, Ropu, and Susupu are still actively using ternate. These 4 villages are located in the coastal area. As a conclusion, given that BT is spoken by less than 100,000 people, it can be said that it is primarily concentrated in coastal areas that are under threat in Sahu district. But since people under 40 continue to speak it, in which on the other hand, reasonably stable.